Universales Morales: la ciencia de la naturaleza humana y el enfoque de la Ética cognitiva - Enrique Fernando Bocardo Crespo (Daimon)
Abstract: Recent trends in Cognitive Ethics have emphasized the conceptual debts with the development of the Science of Human Nature in the late 1600s and early 1700s. The paper deals mainly with two major theoretical approaches in the cognitive revolution, (1) that is possible to offer an explanation of the cognitive mechanisms involved in moral decision processes in terms of abstract principles allegedly embedded in human nature; and (2) that there might be substantive reasons to assume a moral faculty to account for the capacity to issue a potential infinite number of considered moral judgments.